PERMAINAN TRADISIONAL TEPOK ANTRI UNTUK PERKEMBANGAN SOSIAL ANAK USIA 5-6 TAHUN DI DESA ANJUNGAN - Lilis Puji Handayani; Marmawi Marmawi; Lukmanulhakim Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThis study aims to find out and obtain information about how the traditional game of tepok antri can develop socially in children aged 5-6 years in Anjungan Village. The method used in this research is a descriptive method with a qualitative research form. The subjects in this study were 6 children aged 5-6 years and 6 people who had played tepok queuing as children in Anjungan Village. The data collection tools used observation guides, interview guides, and documentation. The results showed that: (1) Empathy can be developed when a child pays attention to a friend who is sad or in distress, (2) Generosity can be developed when a child wants to share a hiding place with other children, (3) Cooperation can help developed when children are compact in playing and obeying existing game rules, (4) caring can be developed when children help friends who fall while playing and need help.Keywords: Tepok Antri Game, Social Development